Metabolic comparison of polycystic ovarian syndrome and control women in Middle Eastern and UK Caucasian populations - Alexandra E. Butler (6189536) (2020)
To determine if metabolic characteristics differed in women with and without polycystic ovary syndrome (PCOS) between a Caucasian and Middle East population. Comparative cross-sectional analysis. Demographic and metabolic data from Middle Eastern women from Qatar Biobank (97 with PCOS, 622 controls) were compared to a Caucasian PCOS biobank in Hull UK (108 with PCOS, 69 controls). In both populations, PCOS women showed a worse cardiovascular risk profile of increased systolic and diastolic blood pressure, increased C-reactive protein (CRP), reduced HDL, insulin resistance as well as increased androgens compared to their respective controls without PCOS. UK women without PCOS had higher systolic and diastolic blood pressures, and increased testosterone results (p < 0.01) compared to Middle Eastern women without PCOS who had higher inflammatory markers (WBC and CRP), HDL and insulin resistance (p < 0.001). UK PCOS women had a higher body mass index, systolic and diastolic blood pressures, triglycerides (p < 0.01), whilst Middle Eastern PCOS women showed increased testosterone, free androgen index, HDL and CRP (P < 0.01). There was no difference in insulin or insulin resistance between the two PCOS cohorts. This study highlights ethnic population differences because, whilst cardiovascular risk indices were increased for both PCOS cohorts, this may be for different reasons: BMI, waist and hip measurements, systolic and diastolic blood pressure, and triglycerides were higher in the UK cohort whilst testosterone, HDL and CRP were higher in the Middle East population. Insulin resistance did not differ between the two PCOS populations despite differences in BMI. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-020-75109-2